Membina Karakter Anak Melalui Program Full Day School Berbasis Nilai-Nilai Kepesantrenan (Studi Kasus di Madrasah Ibtidaiyah Nurul Ummah Kotagede Yogyakarta) - Niam, Zainun Wafiqatun (BELAJEA: Jurnal Pendidikan Islam, 2019)
Character building is an important step in the process of education, especially Islamic education. The occurrence of various forms of immoral behavior from the community, especially students is an increasingly problematic education today. Character building needs to be done early on to students, both within the family and educational institutions. This paper is intended to look at the process of character building in one of the Madrasah Ibtidaiyah institutions in Yogyakarta that applies the Fullday school model with a boarding school education base. The formulation of the problem to be answered is about how the process of implementing the Fullday school system in fostering children's character and how to foster children's character with boarding-based values. The results of the study show that character building through the Fullday school program can run more effectively because the teacher's guidance to students is more intensive. In addition, the planting of the values of the pesantrenan can provide students with supplies, such as serving the parents, living a simple and thrifty life, discipline, and so on. Character education and coaching in MI Nurul Ummah is the parents' choice because education obtained by children outside the home can be guaranteed.